Structure of energy industry in Zambia and Russia - Jerry Mazuba Rawlings Kalubi (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the work is caused by the importance of energy for the economic development of Zambia, which is a country with a developing economy. The main aim of the study is to determine the role of energy in the development of states, to identify the main trends in the functioning of the energy sector in the world, to compare the structure and functioning of the electric power industry in Zambia and Russia, which will help to develop key areas for improving the industry in Zambia to intensify the country's economic growth. The methods used in the study: the methods of scientific cognition, in particular, the method of comparative analysis; the method of generalization and systematization of theoretical concepts; the graphical method for presenting the results obtained, and the method of system analysis. Results. It was ascertained that the electric power industry is traditionally considered as a system-forming sector of the economy of any state. Its importance is related to the influence on all spheres of activity, therefore, the insufficient level of its development leads to significant restrictions on the economic growth and competitiveness of the state. The paper highlights the main world tendencies of the electric power industry: energy efficiency improvement, highlighting the importance of alternative types of energy, constant growth of the total amount of energy consumed in industrialized countries, as well as energy consumption per capita, while in developing countries, it is associated with income growth. A comparative analysis of the structure and functioning of the electric power industry in Zambia and Russia shown that in Zambia a crisis in the electric power industry has been occurring for several years. The author proposed the actions to adapt Russian best practices to improve the effectiveness of this economic sector in Zambia.